2019
DOI: 10.1016/j.engstruct.2019.109552
|View full text |Cite
|
Sign up to set email alerts
|

Progressive collapse resistance of precast concrete beam-column sub-assemblages with high-performance dry connections

Abstract: Due to its relatively lower integrity, precast concrete structures are considered to be more vulnerable to progressive collapse than cast-in-place concrete structures. However, to date, majority of existing studies on progressive collapse focused on cast-in-place concrete structures, little attentions were paid to precast concrete structures. Among existing precast concrete structures, unbonded post-tensioning precast concrete structure is one of innovation dry connection structural systems, which no casting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 34 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…Traditional strengthening methods are used to prevent progressive collapse of RC frame structure, mainly including prestress strengthening method (Qian et al [3,4]), steel Polymers 2021, 13, 1306 2 of 16 bonding strengthening method [5,6], bracing strengthening method [7][8][9], etc. These methods are effective in strengthening of progressive collapse resistance, but the construction is relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional strengthening methods are used to prevent progressive collapse of RC frame structure, mainly including prestress strengthening method (Qian et al [3,4]), steel Polymers 2021, 13, 1306 2 of 16 bonding strengthening method [5,6], bracing strengthening method [7][8][9], etc. These methods are effective in strengthening of progressive collapse resistance, but the construction is relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…e precast concrete frame structure developed by the construction industry has resulted in high production efficiency, better product quality, and low labour intensity [1][2][3][4][5][6]. e mechanisation and standardisation of prefabrication methods have made the production of concrete elements sustainable [7][8][9]. Connections are critical in ensuring structural integrity, adequate strength, energy dissipation, stiffness, and ductility of the designed precast concrete structures [1,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…e failure of connections during natural and humanmade disasters has an adverse impact on precast structures. Precast concrete structures have a relatively low integrity and are more vulnerable to progressive collapse than the traditional cast-in-place concrete structures [9]. e design of precast structures must take into account the occurrence of a fire as it is one of the accidental actions [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it is essential to provide practical recommendations for enhancing the structural robustness of structural configurations of the form considered in this study. Some studies scope on the precast connection's behavior due to progressive collapse, Al-Salloum et al [11], studied how to strengthen the precast connections using bolted steel plates and Qian et al [12], studied the resistance of high-performance dry connections due to progressive collapse. Tang et al [13], studied and designed an asymmetric double-half-span single-column structure with a fully bolted connection in (RCS) frame structure.…”
Section: Introductionmentioning
confidence: 99%